Regime de consolidação em área de preservação permanente e reserva legal no Novo Código Florestal a partir da racionalidade ambiental de Enrique Leff - Vasconcellos, Wagner Eduaurdo (2017)
The following dissertation analyzes the consolidation policy of the permanent preservation areas and legal reserve in the new Forestry Code, according to the Enrique Leff’s environmental rationality theory. The work investigates the legal arrangement of the developing paradigm from the socio environmental rule of law, which aims the neoliberalism overcoming, as a result of the crisis of modernity and its reflexes in environmental area. Afterwards, the assumptions and elements of environmental rationality theory are presented. Environmental crisis is a modern rationality crisis which increased the man-nature segregation, reducing the environment to the condition of natural resources warehouse. The Environmental rationality purposes to overcome nature mercantilizing emphasized in the economic model and the overcoming through a mode of production founded in the entropic limits of nature. Enrique Leff’s theoretical construction claims the necessity of a new environmental epistemology based on the complexity and knowledge dialogue , and a new ethos guided by otherness and a policy of differences. At the end, it is possible to infer that the consolidation model of the protected zones in the new Forestry Code is not compatible with the purpose of the environmental rationality neither with the guidelines of the Ecological Constitution from 1988, since it was limited to reproduce a hyper economical view of the environment.